Pouch-anal cancer after restorative proctocolectomy for familial adenomatous polyposis - Herbay, Axel von; Stern, Josef; Herfarth, Christian (The American journal of surgical pathology, 1996)
Familial adenomatous polyposis (FAP) and idiopathic ulcerative colitis are both mucosal diseases that bear a significant risk of developing colorectal cancer. As a consequence, their surgical treatment is currently widely performed by restorative proctocolectomy with pelvic ileal pouch-anal anastomosis (IPAA). Herein we report a new case of cancer after IPAA that developed in a 33-year-old woman with FAP. Pouch-anal cancer was diagnosed 8 years after restorative proctocolectomy, including anorectal mucosectomy, for FAP with manifest cancer in the sigmoid colon. This case observation reemphasizes that the risk of cancer for FAP patients persists as long as any rectal mucosa remains after IPAA surgery.
Gesehen am 27.08.2025